Role of Investment Opportunity Set (IOS) in Moderating the Influence of Company Size, Activity, and Profitability on Capital Structure in Multi-Industry Sector Companies for the Period 2015–2019 - Christine Dewi Nainggolan; Elly Susanti; Khairul Azwar (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
Growing business competition expects companies to pay more attention to ensuring capital accessibility. Fulfillment of capital needs can be obtained both internally and externally from the company. The purpose of this research is to analyze the influence of firm size, activity, and profitability on capital structure moderated by investment opportunity set in multi-industry sector companies. The population in this research is a multi-industry sector company listed on the Indonesia Stock Exchange, with a research period of 2015 to 2019. The data analysis techniques used in this research are descriptive statistical analysis, classical assumption test, hypothesis test, and residual test for regression moderation analysis on SPSS. The results of this study showed that firm size and activity had a positive and significant effect, while profitability had a significant effect on the capital structure, Investment Opportunity Sets (IOS) play a role in moderating the influence of firm size, activity, and profitability on capital structures. The practical implications on this study, companies that have high investment opportunities it means companies have the opportunity to grow which has an impact on investors’ profits in the future. For companies, it helps managers in determining optimal capital structure policies in maximizing the company’s profit and creating well-being for investors.